(untitled) (World Bulletin of Social Sciences, 2023)
The idea of writing this article arose because of the current discussions. Also, science fiction and fantasy are my favorite genres, they have absolutely unlimited possibilities for expressing different ideas and huge creative potential. I often work with such texts these days. Therefore, I would like to clarify the situation as much as possible